Hydrogen-Bonded Di(hydroperoxy)alkane Adducts of the Type Cy3P=O·(HOO)2CHR (R = Alkyl) - Rahym Ashirov; Maya Todorovic; Nattamai Bhuvanesh; Janet Blümel (Molecules)
Five representatives of a novel type of di(hydroperoxy)alkane adducts of phosphine oxides have been synthesized and fully characterized, including their solubility in organic solvents. The phosphine oxide Cy3PO (1) has been used in combination with the corresponding aldehydes to create the adducts Cy3PO·(HOO)2CHCH3 (2), Cy3PO·(HOO)2CHCH2CH3 (3), Cy3PO·(HOO)2CH(CH2)2CH3 (4), Cy3PO·(HOO)2CH(CH2)3CH3 (5), and Cy3PO·(HOO)2CH(CH2)7CH3 (6). All adducts crystallize easily and contain the peroxide and phosphine oxide hydrogen-bonded in 1:1 ratios. The single crystal X-ray structures of 2–6 and their unique features are discussed. The 31P NMR spectra of the adducts 2–6 show downfield-shifted signals as compared to Cy3PO. In the IR spectra, the ν(P=O) wavenumbers of the adducts have smaller values than the neat phosphine oxide. All spectroscopic results of 2–6 show that the P=O bond is weakened by hydrogen-bonding to the di(hydroperoxy)alkane moieties. Adduct 6 selectively oxidizes PPh3 to OPPh3 within minutes, and nonanal is reformed in the process. The easy synthesis, handling, and administration of these stable, solid, and soluble peroxides with well-defined composition will have a positive impact on synthetic chemistry.